Corrigendum to “Influence of the Crystallinity on the Physicochemical Properties of Spray-Dried Quercetin-Inulin Microparticles and Their Performance During in Vitro Digestion” [Food Chemistry Volume 434 2024 137325 (Food Chemistry 2024 434 s030881462301943x (10.1016/J.Foodchem.2023.137325)) - Gimenez-Castillo, B (Elsevier Ltd, 2024)
The authors regret to have omitted the ANID (Fondecyt Project 3210715) from the funding/acknowledgement section. The authors would like to apologise for any inconvenience caused. © 2024 Elsevier Ltd